SISTEM TENURIAL TANAH ADAT DI BALI: STUDI TANAH PEKARANGAN DESA DI DESA PAKRAMAN BENG - Sulastri, Ni Putu Arie; Guntur, I G Nyoman (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
Strictly speaking, the Basic Agrarian Law is not intended to wipe out someone’s or legal body’s rights but rather to unify the National Land Law. As mentioned at Part II of the Basic Agrarian Law, the conversion had to be done to admit both the western registered lands and those bearing the adat rights. One of the rights that can be converted into the right of ownership is druwe desa land. Eventhough there has already been a rule on the above conversion, druwe desa at Pakraman Beng Village have not been converted up to the present moment. The concept of Tri Hita Karana is one of the reasons why druwe desa still exists. Keywords: Village yard, druwe desa land, conversion stipulation.